A retrospective analysis of the incidence of sports injuries presenting to a primary healthcare clinic in Cape Town. - Tadmor, Daniel Isaac (My University, 2022)
Background: There is a lack of South African specific data related to Sport and Exercise Medicine in the public primary healthcare sector. Primary healthcare affords the majority of the population access to essential healthcare services via clinics and trauma units. Orthopaedic and sports-related injury visits are common and should form part of the basic care provided at this level of health care. Aims and Objectives: The study set out to retrospectively investigate the incidence proportion of sports-related orthopaedic injuries presenting to a primary level government clinic and trauma unit in Cape Town. Furthermore, it aimed to highlight the need for epidemiological sports injury data collection in the public primary healthcare sector in South Africa. Methodology: The data were retrospectively collected using clinical records from 1 July 2017 to 30 June 2019. Sports-related injuries were identified from orthopaedic injury presentations and classified according to demographics and injury patterns. Results: A total of 1346 orthopaedic injuries were identified, resulting in 206 sports related injuries - an incidence proportion of 15.3%. The most common type of sport causing injury was soccer. Most of the injuries occurred acutely, were male, between the ages of 10-19 years, and were soft tissue injuries. There were more upper limb injuries than lower limb injuries and wrist/forearm injuries were the most common type. Conclusion: This study identified the incidence proportion of sport-related injuries in a South African primary healthcare trauma unit. In order to advocate for care at a primary care level, the sports-related injury load needs to be identified. The findings can assist in assessing the need for the South African healthcare system and policy makers to recognise and acknowledge sports injuries and have appropriate facilities that will allow for proper consultation, surveillance, and management of sports related injuries.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, 2022